'UPON THE ELYSIAN STREAM' AN OXFORD COLLEGE BOAT CLUB'S ARCHIVE AND ITS OARSMEN. Issue 130 (April 2015) - Blandford-Baker, Mark
Abstract : This article is based on a paper given to the British Records Association Annual Conference, 26 November 2015 'In a League of their Own: Archives of the History of British Sport and Physical Recreation'. It traces the history of inter-collegiate rowing at Oxford University through the archives of the Magdalen College Boat club.